2021
DOI: 10.3390/atmos12101248
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of Drought: A Case Study of Water-Stressed Region of Pakistan

Abstract: Demand for water resources has increased dramatically due to the global increase in consumption of water, which has resulted in water depletion. Additionally, global climate change has further resulted as an impediment to human survival. Moreover, Pakistan is among the countries that have already crossed the water scarcity line, experiencing drought in the water-stressed Thar desert. Drought mitigation actions can be effectively achieved by forecasting techniques. This research describes the application of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Although the precipitation event is dependent on many dynamic and coupled Frontiers in Environmental Science frontiersin.org processes, which necessitates very complicated coupled simulation models for prediction, the ARIMA model was used to produce a simple and reliable time series analysis. The advantages of ARIMA over traditional statistical and numerical weather prediction approaches have been discussed by (Taneja et al, 2016;Kumar et al, 2021). Much of the tropics and subtropics of the Eastern Hemisphere, as well as a significant amount of the world's population, are influenced by the Asian monsoon circulation (Chattopadhyay, 2007).…”
Section: Figurementioning
confidence: 99%
“…Although the precipitation event is dependent on many dynamic and coupled Frontiers in Environmental Science frontiersin.org processes, which necessitates very complicated coupled simulation models for prediction, the ARIMA model was used to produce a simple and reliable time series analysis. The advantages of ARIMA over traditional statistical and numerical weather prediction approaches have been discussed by (Taneja et al, 2016;Kumar et al, 2021). Much of the tropics and subtropics of the Eastern Hemisphere, as well as a significant amount of the world's population, are influenced by the Asian monsoon circulation (Chattopadhyay, 2007).…”
Section: Figurementioning
confidence: 99%
“…The SPEI measures drought conditions based on the water balance, i.e., the difference between the atmospheric water supply (precipitation) and water demand (i.e., PET) [30]. The calculation procedure of the SPEI is similar to that of the SPI, and the difference is that the SPEI uses climatic water balance (the difference between precipitation and PET) rather than precipitation as an input [46,47]. The size of PET thus affects the calculation of the SPEI.…”
Section: Climate Change Characterized By Global Warming Has Become An...mentioning
confidence: 99%
“…The wide application of the ARIMA model is due to its flexibility and systematic search (identification, estimation, and diagnostic check) for an appropriate model [16]. It has been documented that the ARIMA model can outperform most statistical models, such as exponential smoothing and neural networks, in hydrologic and meteorological time series [46,47].…”
Section: Climate Change Characterized By Global Warming Has Become An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reviews showed that despite numerous studies focused on using specific ML methods on predicting air temperature, few studies are comparing and evaluating the application of multiple ML methods in the same study [35]. Since, temperature has a direct effect on precipitation, which will create drought event, so different ML approaches would help in forecasting drought event [36]. This work could be used as reference for other hydrological and hydro-metrological parameters like rainfall, streamflow measurement etc.…”
Section: Introductionmentioning
confidence: 99%